Analysis of Potential Sectors in Tanimbar Islands Regency - Ferly A. Sairmaly; Paulus Laratmase; Moses Feninlambir; Yani Batmomolin (Yayasan Adra Karima Hubbi, 2024)
Tanimbar Islands Regency, as one of the archipelagic regions in Indonesia, has rich economic potential. However, this potential has not been fully explored and utilized. The study of potential sector analysis in this district is important because it can provide a more in-depth view of economic opportunities that can be developed, contribute to local economic growth, and improve community welfare. This study aims to analyze potential sectors in Tanimbar Islands Regency. The main objective is to identify economic sectors that have potential for further development. In addition, this research also aims to understand the factors that influence economic potential in this district, as well as provide a baseline of information that can be used for future economic development planning. The research method involves collecting secondary data, such as economic statistical data, agricultural data, fisheries data, and other relevant data sources. Data analysis was conducted using statistical tools and economic data analysis techniques. In addition, the research also involved field surveys and interviews with local stakeholders to gain a deeper insight into potential sectors. The results of this study identified several potential sectors in Tanimbar Islands Regency, including agriculture, fisheries, tourism and human resource development. In addition, factors such as accessibility, infrastructure and capitalization also play an important role in the development of these sectors. With the right efforts, these sectors have the potential to contribute significantly to economic growth and improved welfare of the local community. The potential sector analysis study in Tanimbar Islands Regency highlights the economic opportunities that can be optimized to support the development of this area. By understanding the factors that influence economic potential, authorities can direct resources and development efforts more efficiently. By developing these potential sectors, it is expected to create employment opportunities, increase community income, and stimulate sustainable economic growth in Tanimbar Islands Regency.